1, 2-Dichloropropane induces γ-H2AX expression in human cholangiocytes only in the presence of macrophages. (1st October 2021) - Takizawa, Ryoya; Ichihara, Sahoko; Zong, Cai; Kinoshita, Kazuo; Sakurai, Toshihiro; Ikegami, Akihiko; Mise, Nathan; Ichihara, Gaku
Graphical abstract: Highlights: 1, 2-DCP did not increase γ-H2AX-expressing mono-cultured cholangiocytes. γ-H2AX was increased in co-cultured cholangiocytes with macrophages exposed to 1, 2-DCP. 1, 2-DCP induced TNF-α and IL-6 in co-cultured cholangiocytes with macrophages. Macrophages play a critical role in the induction of DNA double strand break by 1, 2-DCP. Abstract: Recent epidemiological studies reported cases of cholangiocarcinoma in workers exposed to 1, 2-dichloropropane (1, 2-DCP) in an offset proof printing factory in Japan. The present study investigated the effects of 1, 2-DCP on the expression of histone family member X (H2AX) phosphorylated on Ser 139 (γ-H2AX), a marker of DNA double strand break, in human immortalized cholangiocytes MMNK-1 cells. Mono-cultures of MMNK-1 cells and co-cultures of MMNK-1 cells with THP-1 macrophages were exposed to 1, 2-DCP at concentrations of 100 and 500 μM for 24 h. Expression of γ-H2AX was visualized by immunofluorescence staining. Exposure to 1, 2-DCP had no effect on the expression of γ-H2AX in mono-cultured MMNK-1 cells, but significantly increased the number of nuclear foci stained by γ-H2AX in MMNK-1 cells co-cultured with THP-1 macrophages. Exposure to 1, 2-DCP also significantly increased the levels of tumor necrosis factor (TNF)-α and interleukin (IL)-6 in co-cultured MMNK-1 cells. The results suggest that macrophages play a critical role by producing cytokines in 1, 2-DCP-induced DNA double strand break in MMNK-1 cells.